واقع استخدام الوسائل التعليمية في التدريس لتلاميذ الشق الثاني من مرحلة التعليم الأساسي العام ببلدية الأبيار - مخلوف , عيسى رمضان محمد (Scientific Journal of University of Benghazi, 2020)
The study aims to identify the extent of awareness among teachers of the second part of basic education in the municipality of Al-Abyaar to the importance of using educational aids, and to know the most important educational methods used in teaching school subjects in the stage of basic education, as well as to identify the obstacles to using educational means at this stage, and the descriptive approach was used The study sample consisted of (89) male and female teachers, 36% of the study population. A questionnaire was designed consisting of (60) statements distributed into three domains, and the Cronbach Alpha coefficient, arithmetic averages, standard deviations and relative weights were used, and the results of the study showed that the sample individuals (average awareness) the importance of educational aids, and that the most important educational methods used In teaching (display devices - blackboard - maps - symbols - computer - and the compound and electronic microscope),And that the most important obstacles to the use of educational aids are (lack of physical and moral functional incentives for male and female teachers who use educational aids - failure to prepare classrooms for the use of educational aids, whether in terms of space or electrical connections, and the high costs and prices of some educational aids, their maintenance and speed of damage - the lack of sufficient numbers. Among the educational aids in basic education schools - the lack of the budget allocated by the school administration for educational aids - the lack of training courses that help teachers use educational aids,The study adopted several recommendations, including (working to provide appropriate financial budgets and material resources that help in the use and implementation of educational aids, and preparing classrooms with the necessary tools, equipment and devices - providing material and moral incentives for teachers and working to encourage them to use educational aids - work on Diversifying educational aids to allow the teacher to choose the most appropriate means according to the different educational situations - to support specialists in the production of educational aids and to overcome the difficulties that hinder their work).